Analisis Kapasitas Tampung Saluran Drainase Ekisting terhadap Debit Banjir Rencana (Studi Kasus: Desa Medaeng, Kecamatan Waru, Kabupaten Sidoarjo) - Kurniawan, Anas; Saves, Faradlillah; Safitri, Dika Ayu (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Flooding problem in Medaeng Village, Waru District, Sidoarjo Regency, is a crucial issue caused by changes in land use, high rainfall, and suboptimal drainage channel conditions and lack of maintenance. Initial studies indicate that drainage channels in Medaeng Village are unable to accommodate large volumes of water, exacerbated by high sediment and dense settlements that reduce infiltration areas. This study aims to analyze the drainage channel capacity based on the design flood discharge. The research method involves primary and secondary data. Analysis of maximum and average rainfall uses the Thiessen Polygon method, frequency distribution analysis uses the Log Pearson Type III method, and the Smirnov-Kolmogorov goodness-of-fit test. Rainfall intensity is calculated using the Mononobe method, design flood discharge calculation uses the rational method, and storage capacity uses the rational method. The results of the analysis show that Qhidrologi is 0.689 m3/s (2 years), 0.855 m3/s (5 years) and 0.955 m3/s (10 years). Meanwhile, the existing Qhydrology is 0.0693 m3/s (channel 1), 0.0588 m3/s (channel 2), 0.2163 m3/s (channel 3), 0.2315 m3/s (channel 4), 0.2491 m3/s (channel 5). The comparison between (Qhydrology>Qhydrology) shows that all channels 1 to 5 have a small capacity and have the potential to cause flood risk. The results of this analysis can be the main basis for technical planning to increase the capacity of the Medaeng Village channels and a reference for further studies on more comprehensive flood mitigation.